Penerapan Model Pembelajaran Problem Based Learning Berbasis Mobile Learning Untuk Menigkatkan Kemampuan Berfikir Kritis Siswa - yani alfani (Trapsila: Jurnal Pendidikan Dasar, 2022)
This study aims to apply a mobile learning-based learning model to improve students' critical thinking skills in science subjects in elementary school. The research conducted was Classroom Action Research. The research objective was to improve critical thinking skills in the science subject in class IV SD Negeri 10 Tumang through the implementation of mobile learning-based Problem Based Learning models in learning. In this study the authors used the PTK model put forward by Kemmis and Mc.Taggart. Data collection techniques used by researchers in this study were tests and non-tests. Based on the results of research that has been carried out by applying the mobile learning-based Problem Based Learning (PBL) learning model, it can improve students' critical thinking skills in grade 4 SDN 10 Tumang